Ultra-low-dose chest computed tomography without anesthesia in the assessment of pediatric pulmonary diseases - Cristina Manera Dorneles; Gabriel Sartori Pacini; Matheus Zanon; Stephan Altmayer; Guilherme Watte; Marcelo C. Barros; Edson Marchiori; Matteo Baldisserotto; Bruno Hochhegger (Elsevier, 2020)
Objective: To evaluate the feasibility of using ultra-low-dose computed tomography of the chest with iterative reconstruction without anesthesia for assessment of pulmonary diseases in children. Methods: This prospective study enrolled 86 consecutive pediatric patients (ranging from 1 month to 18 years) that underwent ultra-low-dose computed tomography due to suspicion of pulmonary diseases, without anesthesia and contrast. Parameters used were: 80 kVp; 15-30 mA; acquisition time, 0.5 s; and pitch, 1.375. The adaptive statistical iterative reconstruction technique was used. Subjective visual evaluation and quantitative assessment of image quality were done using a 5-point scale in 12 different structures of the chest. Results: Mean age was 66 months (interquartile range, 16-147). Final diagnosis was performed in all exams, and 44 (51.2%) were diagnosed with cystic fibrosis, 27 (31.4%) with bronchiolitis obliterans, and 15 (17.4%) with congenital pulmonary airways malformations. Diagnostic quality was achieved in 98.9%, of which 82.6% were considered excellent and 16.3% were slightly blurred but did not interfere with image evaluation. Only one case (1.2%) presented moderate blurring that slightly compromised the image, and previous examinations demonstrated findings compatible with bronchiolitis obliterans. Mean effective radiation dose was 0.39 ± 0.15 mSv. Percentages of images with motion artifacts were 0.3% for cystic fibrosis, 1.3% for bronchiolitis obliterans, and 1.1% for congenital pulmonary airways malformations. Conclusion: Chest ultra-low-dose computed tomography without sedation or anesthesia delivering a sub-millisievert dose can provide image quality to allow identification of common pulmonary anatomy and diseases. Resumo: Objetivo: Avaliar a viabilidade do uso de tomografia computadorizada com ultrabaixa dose com reconstrução iterativa sem anestesia para avaliação de doenças pulmonares em crianças. Métodos: Este estudo prospectivo envolveu 86 pacientes pediátricos consecutivos (um mês a 18 anos) submetidos à tomografia computadorizada com ultrabaixa dose por suspeita de doenças pulmonares, sem anestesia e contraste. Os parâmetros utilizados foram: 80 kVp; 15-30 mA; tempo de aquisição, 0,5 s; e pitch de 1,375. Foi utilizada a técnica de reconstrução estatística adaptativa iterativa. A avaliação visual subjetiva e a avaliação quantitativa da qualidade da imagem foram feitas com uma escala de 5 pontos em 12 estruturas do tórax. Resultados: A média de idade foi de 66 meses (intervalo interquartil, 16-147). O diagnóstico final foi feito em todos os exames e 44 (51,2%) foram diagnosticados com fibrose cística, 27 (31,4%) com bronquiolite obliterante e 15 (17,4%) com malformação congênita pulmonar das vias aéreas. A qualidade diagnóstica foi alcançada em 98,9% dos casos, dos quais 82,6% foram considerados excelentes e 16,3% alteração leve na definição, mas isso não interferiu na avaliação da imagem. Apenas um caso (1,2%) apresentou alteração moderada na definição, comprometeu discretamente a imagem, e exames prévios demonstraram achados compatíveis com bronquiolite obliterante. A dose de radiação média efetiva foi de 0,39 ± 0,15 mSv. As porcentagens de imagens com artefatos de movimento foram de 0,3% para fibrose cística, 1,3% para bronquiolite obliterante e 1,1% para malformação congênita pulmonar das vias aéreas. Conclusão: É possível realizar a tomografia computadorizada com ultrabaixa dose torácica sem sedação ou anestesia, administrando uma dose de submilisievert, com qualidade de imagem suficiente para a identificação pulmonar anatômica e de doenças pulmonares comuns. Keywords: Computed tomography, Thorax, Ultra-low-dose radiation, Iterative reconstruction, Pediatric patients, Palavras-chave: Tomografia computadorizada, Tórax, Radiação de dose ultrabaixa, Reconstrução iterativa, Pacientes pediátricos